Theoretical determination of influence of forces of friction on instantaneous forces of cutting, which cause wear of beet-cutting knives - Фабричнікова, І.А. (Problems of Tribology, 2014)
The theoretical researches of process formation of the beet shaving are sets out in article, which allow to estimate more precisely the dynamics of cutting process and influence on diminishing of forces of friction in the process of cutting away of beets and wear of beet-cutting knives.